In vitro Incubation of Platelets with oxLDL Does Not Induce Microvesicle Release When Measured by Sensitive Flow Cytometry - Nielsen, Tine Bo; Nielsen, Morten Hjuler; Handberg, Aase (Frontiers in Cardiovascular Medicine, 2015)
Microvesicles (MVs) are submicron vesicles with sizes of 0.1-1.0-µm in diameter, released from various cell types upon activation or apoptosis. Their involvement in a variety of diseases has been intensively investigated. In blood, platelets are potent MV secretors, and oxLDL, a platelet ligand, induce platelet activation and thus potentially MV secretion. This interaction occurs through binding of oxLDL with CD36, located on the platelet membrane. In this study we investigated the effect of in vitro incubation of platelets with oxLDL on MV release. Furthermore, we compared the results obtained when separating MVs larger than 0.5-µm as a measure of results obtained from less sensitive conventional flow cytometers with MVs below the 0.5-µm limit. MV size-distribution was analysed in plasma from 11 healthy volunteers (4 females, 7 males). MVs were identified as < 1-μm and positive for lactadherin binding and cell specific markers. Platelet rich plasma (PRP) was incubated without and with oxLDL or LDL (as control) to investigate the impact on platelet activation, evident by release of MVs. Size-calibrated fluorescent beads were used to establish the MV gate, and separate small- and large-size vesicles. CD41+ and CD41+CD36+ MVs increased by 6-8 fold in PRP, when left at room temperature, and the presence of cell specific markers increased. Total MV count was unaffected. Incubations with oxLDL did not increase the MV release or affect the distribution of small- and large-size MVs. We found a large inter-individual variation in the fraction of small- and large-size MVs of 73%. In conclusion, we propose that pro-coagulant activity and activation of platelets induced by interaction of platelet CD36 with oxLDL may not involve release of MVs. Furthermore, our results demonstrate great inter-individual variability in size-distribution of platelet derived MVs and thereby stresses the importance for generation of standardized protocols for MV quantification by flow cytometry.